Political changes in Taiwan under Ma Ying-Jeou : partisan conflict, policy choices, external constraints and security challenges - Cabestan, Jean-Pierre.; deLisle, Jacques, 1961- (London : Routledge, 2014)
'In 2008 Ma Ying-jeou was elected President of Taiwan, and the Kuomintang (KMT) returned to power after eight years of rule by the Democratic Progressive Party (DPP). Since taking power, the KMT has faced serious difficulties, as economic growth has been sluggish, society has been polarised over issues of identity and policy, and rapprochement between Taipei and Beijing has met with suspicion or reservation among large segments of Taiwanese society. Indeed, while improved relations with the United States have bolstered Taiwan's security, warming cross-Strait relations have in turn made Taiwan more dependent upon and vulnerable to an increasingly powerful China. This book provides a comprehensive analysis of the return of the KMT to power, and examines the significant domestic political, economic, social and international challenges and changes that have characterized Taiwan since 2008. It identifies the major domestic, cross-Strait and foreign policy trends, and addresses key issues such as - elections and Taiwan's party system; - the role of the presidency and legislature; - economic development; social movements; - identity politics; - developments in cross-Strait relations; - Taiwan's security environment and national defence policies; - relations with the US and Japan. In turn, the contributors look towards the final years of Ma's presidency and beyond, and the structural realities - both domestic and external - that will shape Taiwan's future'--
Introduction / Jean-Pierre Cabestan & Jacques deLisle -- Continuity in the 2012 presidential and legislative elections / Nathan F. Batto -- Taiwan's party system in the Ma Ying-jeou era / Dafydd Fell -- The role of the legislative Yuan under Ma Ying-jeou : the case of China-policy legislations and agreements / Dai Shih-chan & Wu Chung-li -- Taiwan's economy in the shadow of ECFA / Douglas Fuller -- The resurgence of social movements under the Ma Ying-jeou government (2008-2012) : a political opportunity structure perspective / Ho Ming-sho -- Revisiting identity politics under Ma Ying-jeou / Christopher R. Hughes -- Ma Ying-jeou's rapprochement policy : cross-strait progress and domestic constraints / Liu Fu-kuo -- Mainland China's peaceful development strategy and cross-strait relations / Chu Shulong -- Better or worse? : Taiwan's changing security environment / Gudrun Wacker -- Taiwan's national defense transformation, Taiwan's security and US-Taiwan relations / Lin Cheng-yi -- US-Taiwan relations since 2008 / Richard Bush -- Japan-Taiwan relations since 2008 : an evolving practical, not strategic, partnership / Ryo Sahashi -- Taiwan in international organizations / Sigrid Winkler -- Taiwan and soft power : contending with China and seeking security / Jacques deLisle.
Includes bibliographical references and index.
Keywords: Ma, Yingjiu; Taiwan -- Politics and government -- 2000-; Taiwan -- Foreign relations -- 21st century; Taiwan -- International status